Myxoid liposarcoma of small bowel presenting with intussusception and obstruction: A case report - Monis, Mohd; Koppal, Divyashree; Ibbrahim, Aiman; Nahid, Zeeshan (Indian Journal of Case Reports, 2021)
Gastrointestinal liposarcomas are extremely rare with the most common reported morphological subtype being dedifferentiated liposarcoma and well-differentiated liposarcoma. These tumors are rarely diagnosed preoperatively and diagnosis is only confirmed on histopathological analysis. Treatment of gastrointestinal liposarcomas consists of surgical excision with widely negative margins followed by post-operative irradiation and close follow-up. We report an exceedingly rare case of myxoid liposarcoma of the small bowel (ileum) presenting with an unusual presentation with intussusception and intestinal obstruction. A 42-year-old male presented to the emergency department with features of intestinal obstruction. Contrast-enhanced computed tomography abdomen revealed ileo-ileal intussusception with an endoluminal soft-tissue lesion at the leading edge. The patient was taken for surgical intervention and the involved segment of the bowel along with the lesion was resected and re-anastomosis done. Histological sections of the mass along with immunohistochemistry suggested the pathological diagnosis of myxoid liposarcoma.